Penerapan Kurikulum Merdeka pada Mata Pelajaran Pendidikan Pancasila - Indira Rohmawati; Suttrisno Suttrisno (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The curriculum greatly influences the education system in Indonesia. This is evident from the fact that the education system in Indonesia has experienced various changes since the past, but there is still room for improvement in facing global challenges. Currently, the education system in Indonesia implements education based on the